Evaluasi Ketahanan Galur International Rice Bacterial Blight terhadap Hawar Daun Bakteri dan Identifikasi Patotipe Xanthomonas oryzae pv. oryzae Provinsi Jawa Tengah Berdasarkan Galur IRBB - Dini Yuliani; Wage Ratna Rohaeni; . Sudir (Institut Pertanian Bogor, 2018)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is the major disease in rice plants causing considerable economic losses. The objective of the study was to evaluate the resistant International Rice Bacterial Blight (IRBB) lines against bacterial leaf blight and the identification of Xoo pathotype from Central Java Province as the basis recommendation of the resistant varieties assembly with the background of resistant genes to overcome BLB disease. The evaluation of Xoo isolates from 22 districts in Central Java Province on IRBB lines was conducted in the rainy season 2016-2017 using split plot with three replications. The main plot was 15 IRBB lines, while the subplot was 110 Xoo isolates. Among 15 lines of IRBB, there were 10 lines have functioned as pathotype examiner of Xoo. The results obtained 6 lines were reacted resistant, namely IRBB5, IRBB7, IRBB8, IRBB57, IRBB64, and IRBB66. The IRBB66 line can be used as a resistant elder for the assembly of BLB resistant varieties because it has a combination of pyramiding resistant genes that were effective against BLB in some areas of Central Java Province. Pathotype IX was only found and dominant in Pemalang. Pathotype X was obtained in six districts of Tegal, Brebes, Banjarnegara, Purbalingga, Purworejo, and Grobogan. Pathotype XII was the most dominant prototype in 15 districts. Assembling of resistant varieties with resistant gene backgrounds based on the existence of a specific Xoo pathotype in the field can reduce the severity of BLB disease.